Differential regulation of synthesis of multiple forms of specific endoglucanases by Trichoderma reesei QM9414. - Messner, R (1988)
A method consisting of sodium dodecyl sulfate-polyacrylamide gel electrophoresis and subsequent detection of endoglucanases by blotting with a polyclonal antibody against endoglucanase I was used to investigate the effect of induction and carbon catabolite derepression on the synthesis of multiple forms of endoglucanase I by Trichoderma reesei. Five forms appeared upon growth on cellulose, whereas four and only two appeared upon growth on lactose (carbon catabolite derepression) and induction by sophorose in a resting cell system, respectively. All endoglucanases detected resembled endoglucanase I in their specificity, since they exhibited no activity toward xylan or paranitrophenyl-beta-D-lactobioside. A small (25-kilodalton) endoglucanase only appeared during growth on cellulose. None of the multiple forms arose by postsecretional modification. The results indicate that sophorose may not be the only compound mediating cellulose induction of the specific endoglucanases in T. reesei.